Chest pain, shortness of breath, and palpitations unmask an unexpected diagnosis - Schweizer, Patrick Alexander; Korosoglou, Grigorios; Thomas, Dierk; Aulmann, Sebastian; Remppis, Bjoern-Andrew; Witzens-Harig, Mathias; Katus, Hugo (Circulation, 2012)
A 48-year-old white man was admitted to our hospital because of a sustained wide-complex tachycardia (160 bpm). He presented with chest discomfort, dyspnea, palpitations, and dizziness. Because medical cardioversion with intravenous amiodarone failed, intravenous ajmaline was administered, which successfully resulted in conversion to sinus rhythm. Physical examination and laboratory results revealed no significant abnormalities. The patient reported no discomfort until the morning of admission, and there was no history of disease except for tuberculosis, successfully treated 20 years earlier. Although serial cardiac troponin T analysis was negative, the patient complained of ongoing angina. Cardiac catheterization showed subtotal stenosis of the right coronary artery (Figure 1A), which was successfully treated by percutaneous coronary intervention and placement of a bare-metal stent (Figure 1B). Notably, the coronary arteries showed no high-grade lesions in the other main coronary vessels. Echocardiography revealed an echodense mass at the right ventricular lateral wall, the interatrial and interventricular septum, and the left atrial wall. A magnetic resonance imaging scan (Figures 2A and 2B; online-only Data Supplement Movies I-IV) calculated a tumor volume of ≈130 mL …